Composite film and preparation method thereof, structural member and electronic product
By forming nanopores on the surface of the AlSiON film and coating it with a functional coating, the problems of low hardness and poor wear resistance of electronic product buttons are solved, realizing a high-hardness and wear-resistant composite film, which improves the stability and durability of the buttons.
Patent Information
- Application Number
- CN202511029514.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-11-25
AI Technical Summary
The materials used for buttons on existing electronic products have low hardness and poor wear resistance, making them easily scratched by bumps and knocks. In addition, the overall hardness of existing protective films is low, making them prone to problems such as peeling and scratches.
Nanopores are formed on the surface of the AlSiON film layer of the main film layer, and a functional coating is coated on it. The nanopores provide good adhesion points, increasing the bonding force between the functional coating and the main film layer, forming a high-hardness and wear-resistant composite film.
It significantly improves the wear resistance and stability of the composite film, enhances the adhesion between the functional coating and the main film layer, prevents shear stress and peel stress, and extends the service life of electronic product buttons.
Smart Images

Figure CN121006508A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of materials, in particular to a composite film and a preparation method thereof, a structural member and an electronic product. BACKGROUND
[0002] The substantial increase in daily use time of electronic products puts forward higher requirements on the durability of product appearance. The keys of products such as mobile phones, electronic watches and electronic cigarettes have a very high frequency of daily use, and their durability and stability are tested.
[0003] At present, the key material used by electronic products on the market is generally plastic. The plastic key is soft in texture and poor in wear resistance, and is easy to be scratched by knocking.
[0004] To solve these problems, a protective film is often constructed on the surface of the key, and the formation method of the protective film generally includes chemical anodizing, chemical plating, pasting a protective film or using PVD technology. Among them, the protective film pasted on the surface or formed by PVD deposition has low overall hardness, poor durability, and is prone to problems such as film falling off and scratching.
[0005] Therefore, it is of great significance to develop a composite film with high hardness and wear resistance. SUMMARY
[0006] The embodiment of the present application provides a composite film and a preparation method thereof, a structural member and an electronic product, the composite film comprising a main film layer and an AlSiON film layer existing on at least one side of the main film layer; a nano-pore is arranged on the surface of the side of the AlSiON film layer away from the main film layer, and the average pore diameter of the nano-pore is 4-25nm. By forming a nano-pore on the surface of the AlSiON film layer, the functional coating added subsequently according to the application needs can be better combined on the surface of the AlSiON film layer, so that a composite film with high hardness and wear resistance is obtained.
[0007] In a first aspect, the embodiment of the present application provides a composite film, comprising: a main film layer and an AlSiON film layer existing on at least one side of the main film layer.
[0008] The AlSiON film layer is provided with a nano-pore on the surface of the side away from the main film layer, and the average pore diameter of the nano-pore is 4-25nm.
[0009] In a possible implementation, the average depth of the nano-pore is 5-55nm.
[0010] In a possible implementation, the average pore diameter of the nano-pore is 10-20nm.
[0011] And / or, the average depth of the nano-pore is 15-30nm.
[0012] In a possible implementation, the AlSiON film layer has a thickness greater than or equal to 200 nm; preferably, the thickness is 200 nm-300 nm.
[0013] In a possible implementation, the main film layer comprises first refractive index film layers and second refractive index film layers arranged alternately; the first refractive index film layers have a refractive index greater than that of the second refractive index film layers.
[0014] In a possible implementation, the main film layer further comprises a transition film layer.
[0015] At least one of the first refractive index film layers and at least one of the second refractive index film layers form a sub-composite layer, and the transition film layer is located between any two sub-composite layers.
[0016] In a possible implementation, the first refractive index film layers in the sub-composite film layers on both sides of the transition film layer are made of different materials.
[0017] In a possible implementation, the transition film layer has a refractive index greater than or equal to 2.05.
[0018] In a possible implementation, the transition film layer has a thickness greater than or equal to 100 nm; preferably, the thickness is 100 nm-200 nm.
[0019] In a possible implementation, the first refractive index film layer is made of at least one of SiN, AlN, AlSiN, and AlSiON.
[0020] In a possible implementation, the second refractive index film layer is made of at least one of SiO2 and Al2O3.
[0021] In a possible implementation, the transition layer is made of AlSiN.
[0022] In a possible implementation, the composite film further comprises a functional coating layer.
[0023] The functional coating layer comprises a convex part embedded in a nano-pore on the surface of the AlSiON film layer and a flat part covering a flat part of the surface of the AlSiON film layer.
[0024] The flat part of the functional coating layer has a thickness of 15-35 nm.
[0025] In a possible implementation, the composite film further comprises a primer layer; the primer layer is located on the opposite side of the main film layer on which the AlSiON film layer is located.
[0026] Preferably, the primer layer has a thickness of 5-50 nm.
[0027] Preferably, the material of the primer layer comprises Al2O3.
[0028] In a possible implementation, the thickness of the sub-composite layer between the AlSiON film layer and the transition film layer is greater than or equal to 500 nm.
[0029] And / or, the thickness of the sub-composite layer between the primer layer and the transition film layer is greater than or equal to 400 nm.
[0030] In a possible implementation, the thickness of the composite film is greater than or equal to 1100 nm, preferably 1100 nm-1800 nm.
[0031] In a second aspect, the embodiments of the present application provide a preparation method of the composite film, comprising:
[0032] Preparation of a substrate, formation of an initial composite layer on the substrate, and the AlSiON film layer on the side of the initial composite layer away from the substrate;
[0033] Forming nano-pores on the surface of the AlSiON film layer away from the initial composite layer to obtain the composite film on the surface of the substrate.
[0034] In a possible implementation, the preparation method of the composite film further comprises:
[0035] Coating a coating liquid for forming a functional coating on the surface of the AlSiON film layer with nano-pores to form the functional coating.
[0036] In a possible implementation, the initial composite layer is formed on the substrate, and the preparation method of the composite film further comprises:
[0037] Forming a primer layer on the substrate before forming the initial composite layer.
[0038] In a possible implementation, the forming of nano-pores on the surface of the AlSiON film layer away from the initial composite layer comprises:
[0039] Immersion of the initial composite layer in an etching liquid, and heating the etching liquid to 50-60℃ for 2-5 min, and then heating to 70-80℃ for 8-10 min; after the formation of nano-pores on the surface, washing and drying.
[0040] In a third aspect, the embodiments of the present application provide a structural member comprising the composite film or the composite film prepared by the preparation method.
[0041] In a possible implementation, the structural member comprises a metal member, and the composite film is arranged on a surface of the metal member.
[0042] In a possible implementation, the structural member is a key of an electronic product.
[0043] In a fourth aspect, an embodiment of the present application provides an electronic product, comprising the structural member.
[0044] The composite film, the preparation method thereof, the structural member and the electronic product provided by the embodiments of the present application can form nanometer holes with an average pore size of 4-25 nm by micro-etching the surface of the AlSiON film layer on at least one side of the main film layer, so that a functional coating added according to application needs can form a more stable adhesive force with the main film layer, and finally, the wear resistance of the surface of the composite film is improved. BRIEF DESCRIPTION OF DRAWINGS
[0045] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0046] Figure 1 A structural diagram of the main film layer and the AlSiON film layer in the composite film provided by the embodiments of the present application;
[0047] Figure 2 A structural diagram of the composite film comprising a primer layer provided by the embodiments of the present application;
[0048] Figure 3 A structural diagram of the composite film provided by Embodiment 1 of the present application;
[0049] Figure 4 A diagram of the surface of the AlSiON film layer after micro-etching provided by Embodiment 1 of the present application;
[0050] Figure 5 A sectional diagram of the composite film provided by Embodiment 1 of the present application.
[0051] BRIEF DESCRIPTION OF DRAWINGS
[0052] 100 - functional coating;
[0053] 101 - protruding part;
[0054] 102 - flat part.
[0055] The above drawings have shown the specific embodiments of the present application, and more detailed descriptions will be given hereinafter. These drawings and textual descriptions are not intended to limit the scope of the concept of the present application by any means, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. Detailed Implementation
[0056] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numbers in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this application as detailed in the appended claims.
[0057] In the existing technology, the buttons used in electronic products have technical problems such as low hardness and poor wear resistance.
[0058] The composite membrane, its preparation method, and its application provided in this application include a main membrane layer and an AlSiON membrane layer present on at least one side of the main membrane layer. By setting nanopores on the surface of the AlSiON membrane layer away from the substrate, the technical problems of poor wear resistance and low hardness of the composite membrane are solved.
[0059] The technical solution of this application and how the technical solution of this application solves the above-mentioned technical problems will be described in detail below with reference to specific embodiments and accompanying drawings.
[0060] This application provides a composite membrane, such as Figure 1 As shown, the composite membrane includes a main membrane layer and an AlSiON membrane layer present on at least one side of the main membrane layer;
[0061] The AlSiON film has nanopores on the side of its surface away from the main film, and the average pore size of the nanopores is 4-25 nm.
[0062] The composite membrane provided in this application includes a main film layer and an AlSiON film layer present on at least one side of the main film layer. Because AlSiON combines the excellent chemical inertness of alumina with the stability of silicon nitride, it exhibits high resistance to various chemical substances (including water vapor, weak acids, weak alkalis, salt spray, etc.), effectively protecting other film layers in the main film layer from environmental corrosion and chemical erosion. Furthermore, the hardness of AlSiON is significantly higher than that of pure SiO2 film, approaching or even exceeding that of Al2O3 and Si3N4. Using it as the outer layer protecting the main film layer in the composite membrane provides excellent scratch and wear resistance, protecting the main film layer from mechanical damage and the substrate from corrosion.
[0063] It should be noted that the AlSiON film mentioned above refers to the film formed using AlSiON material.
[0064] The surface of the AlSiON film layer on at least one side of the main film layer is micro-etched to form a plurality of nano-holes. These nano-holes can provide good attachment points for the functional coating. When a functional coating is applied on the surface of the composite film, the functional coating will flow into and fill the nano-holes. As the functional coating solidifies or forms a film, the coating filled in the nano-holes will be "locked" inside. This physical interlocking structure greatly increases the force required to peel off the functional coating from the AlSiON film layer. Even if there is a weak boundary layer or insufficient chemical bonding force at the interface, this mechanical anchoring can provide strong bonding force, significantly resisting shear stress and peeling stress, thereby greatly improving the adhesion of the functional coating to the main film layer and the overall wear resistance of the composite film.
[0065] When the average pore size and / or average depth of the nano-holes on the surface of the AlSiON film layer are too small, the functional coating will not penetrate into the raised portions formed by the nano-holes in the AlSiON film layer, and will not form a strong embedding effect with the AlSiON film layer, resulting in a decrease in the wear resistance and poor stability of the resulting composite film. When the average pore size and / or average depth of the nano-holes on the surface of the AlSiON film layer are too large, the film structure of the AlSiON film layer is severely damaged, and cannot achieve good protection.
[0066] Considering that the average pore size and / or average depth of the nano-holes can affect the adhesion between the functional coating and the AlSiON film layer, and in turn affect the wear resistance of the composite film, in this application, the average pore size of the nano-holes formed on the surface of the AlSiON film layer is limited to 4-25 nm, and exemplary values can be 4 nm, 7 nm, 10 nm, 13 nm, 15 nm, 18 nm, 20 nm, 25 nm, or any range formed by any two of these values.
[0067] Further, to improve the adhesion of the functional coating to the main film layer, the average depth of the nano-holes formed on the surface of the AlSiON film layer is limited to 5-55 nm, and exemplary values can be 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, or any range formed by any two of these values.
[0068] Further, when the average pore size of the nano-holes is 10-20 nm and / or the average depth is 15-30 nm, the adhesion of the functional coating to the AlSiON film layer is stronger, and the wear resistance of the surface of the resulting composite film is better.
[0069] Exemplarily, the average pore size of the nanopores can be 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, or a range between any two of them.
[0070] Exemplarily, the average depth of the nanopores can be 15 nm, 17 nm, 19 nm, 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, or a range between any two of them.
[0071] Since micro-etching needs to be performed on the AlSiON film layer, the thickness of the AlSiON film layer is reduced, the internal structure is changed, and the nanopores have a certain size. Therefore, in order to ensure the compactness and hardness of the overall structure of the main film layer and improve the bonding force of the functional coating on the AlSiON film layer, the thickness of the AlSiON film layer needs to be greater than or equal to 200 nm. In an optional specific embodiment, the thickness of the AlSiON film layer is preferably 200 nm to 300 nm, including but not limited to 225 nm, 265 nm, 288 nm, and the like. Other values conforming to the above range can also be used.
[0072] In the main film layer, first refractive index film layers and second refractive index film layers are arranged alternately; the refractive index of the first refractive index film layers is greater than the refractive index of the second refractive index film layers.
[0073] In the present application, the main film layer is arranged in a multi-film layer manner. When an external force causes dislocations (crystal defects) in the main film layer and attempts to slip, the interfaces between the film layers of different materials become a strong obstacle, and the dislocations are difficult to pass through the interfaces with different crystal structures, lattice constants, and chemical bonds. To make the entire main film layer plastically deform, a greater stress is needed to drive the dislocations to pass through numerous interfaces. In addition, when micro-cracks are generated on the surface or subsurface of the main film layer due to stress, the cracks will tend to expand along the relatively weak interface when they encounter the interlayer interface during the expansion process, rather than penetrating vertically through all the film layers. This can greatly increase the path length of crack propagation, thereby significantly improving the wear resistance of the main film layer.
[0074] In addition, the difference in refractive index represents the difference in atomic structure, bonding, and crystal structure contained in the film layers. The film layers formed by materials with different refractive indices also have dislocation / crack obstacles. Therefore, by alternately arranging the first refractive index film layers and the second refractive index film layers to form the main film layer with a multi-film layer structure, the yield strength and hardness of the main film layer can be effectively improved.
[0075] In the composite film, a transition film layer is further included. The transition film layer is located between any two groups of the sub-composite layers, each of which is composed of at least one first refractive index film layer and at least one second refractive index film layer. In some optional embodiments, the sub-composite layers on both sides of the transition film layer each contain a first refractive index film layer of different material.
[0076] When the materials of the first refractive index film layers contained in different sub-composite layers are different, if no transition film layer is arranged between different sub-composite layers, the first refractive index film layer included in one group of sub-composite layers directly contacts the second refractive index film layer included in another group of sub-composite layers, and the material in the first refractive index film layer and the second refractive index film layer has a large difference in crystal structure, which causes a high film stress between the two film layers. Moreover, for the first refractive index film layers contained in adjacent different sub-composite layers, even if a second refractive index layer is arranged between the two different first refractive index layers, the existence of the second refractive index layer has little effect on relieving the stress between the two adjacent different sub-composite layers. In order to effectively reduce the film stress between adjacent sub-composite layers and obtain a composite film with better wear resistance, the present application arranges a transition film layer between adjacent different sub-composite layers, so that the crystal structure of adjacent different sub-composite layers in the main film layer can continuously change, the lattice mutation between nanometer film layers is eliminated, the dislocation density is greatly reduced, and the problem of weak chemical bonding force and low interface support force between the main film layers is solved, thereby improving the wear resistance of the obtained composite film.
[0077] In order to obtain a composite film with more excellent performance, the material of the transition film layer has a refractive index of not less than 2.05, and the thickness of the transition film layer is greater than or equal to 100 nm. In optional embodiments, the thickness of the transition film layer can be 100 nm-200 nm, including but not limited to 163 nm, 172 nm, 177 nm, and the like, and other values within the above range can also be used.
[0078] The material with a refractive index of not less than 2.05 is selected as the transition film layer, which not only can optimize the optical performance of the main film layer and adjust the visual effect of the composite film, but more importantly, the transition film layer has excellent water and oxygen barrier properties and structural compactness, which can relieve the thermal stress inside the obtained composite film, enhance the interlayer adhesion, and support the nanostructure interface.
[0079] Because there is a thickness uniformity error when depositing the main film layer, there is stress between film layers of different thicknesses. The transition film layer with a thickness of greater than or equal to 100 nm can build a stable stress gradient between the film layers on both sides, thereby avoiding the occurrence of micro-cracks due to stress concentration. In addition, the transition film layer with a certain thickness has relatively high compactness, which can also provide a certain degree of barrier property.
[0080] Specifically, the material forming the different film layers in the main film layer can be selected from AlSiN, SiN, AlN, ZrN, SiON, AlON, Al2O3, ZrO2, CeO2, NB2O5, SiO2, SiH4, TiN, CrN, SiCrC, SiCrNC, etc. The above-mentioned materials not only have high hardness, but also have excellent wear resistance and barrier properties, which can protect sensitive devices.
[0081] The material of the first refractive index film layer contained in the main film layer is selected from at least one of SiN, AlN, AlSiN and AlSiON, and the material of the second refractive index film layer contained in the main film layer is selected from at least one of SiO2 and Al2O3.
[0082] Referring to Figure 2 Specifically, when the material of the first refractive index film layer is selected from SiN and AlN, and the material of the second refractive index film layer is selected from SiO2, the alternating structure of the main film layer is arranged from the side close to the substrate, and a part can be an AlN / SiO2 alternating composite layer composed of SiO2 film layer-AlN film layer-SiO2 film layer-AlN film layer-…-SiO2 film layer-AlN film layer, and another part can be a SiN / SiO2 alternating composite layer composed of SiO2 film layer-SiN film layer-SiO2 film layer-SiN film layer-…-SiO2 film layer-SiN film layer, and a transition film layer formed by AlSiN material can be arranged between the two parts of the composite layer. AlSiN contains Al-N-Si mixed bonds, which has both ionicity and covalence, and can be strongly coupled with the Al-N bonds (bond energy 290 kJ / mol) of the SiO2 / AlN alternating composite layer and the Si-N bonds (bond energy 435 kJ / mol) of the SiO2 / SiN alternating composite layer, thereby realizing higher bonding strength between the AlN / SiO2 alternating composite layer and the SiN / SiO2 alternating composite layer. Figure 2
[0083] Referring to Figure 3 The composite film can further include a functional coating layer 100, which includes a protruding part 101 embedded in the surface nanopores of the AlSiON film layer and a flat part 102 covering the surface of the AlSiON film layer.
[0084] Specifically, the functional coating 100 is a film layer structure formed by applying a functional coating capable of forming the functional coating to the surface of the AlSiON film layer having a nano-pore structure, and the functional coating flows into the nano-pores and solidifies into a film, thereby forming the functional coating 100. The nano-pores on the surface of the AlSiON film layer form a chimeric interlocking structure between the functional coating 100 and the AlSiON film layer, and this physical interlocking structure greatly increases the force required to peel the functional coating from the AlSiON film layer, even if there is a weak boundary layer or insufficient chemical bonding at the interface. This mechanical anchoring provides strong bonding force, significantly resisting shear stress and peeling stress, thereby greatly improving the wear resistance of the overall composite film. Further, in order to improve the service life of the composite film, the thickness of the flat portion 102 of the functional coating 100 is 15-35 nm, including but not limited to 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, etc., and other values within the above range can also be used.
[0085] In specific embodiments, the functional coating includes an anti-fingerprint coating, a water-repellent coating, etc., which can be selected according to actual application requirements, and will not be further limited herein.
[0086] Considering that the atomic structure and lattice structure between compounds of the same element are more similar and the combination is more firm, the composite film further includes a primer layer, such as Figure 3 As shown, the primer layer is located on the opposite side of the main film layer on which the AlSiON film layer is located. Considering that the function of the primer layer is to appropriately fill the substrate surface to form a high-surface-energy base layer, facilitating the deposition of subsequent film layers. Therefore, the thickness of the primer layer is 5-50 nm, including but not limited to 5 nm, 12 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc. Specifically, in order to have a good bonding force between the main film layer and the primer layer, the material of the primer layer can be selected according to the characteristics of the substrate and the structure of the main film layer, and specifically can be Al2O3 or the like.
[0087] In the present application, the thickness of the main film layer between the primer layer and the transition film layer is greater than or equal to 400 nm; and the thickness of the main film layer between the AlSiON film layer and the transition film layer is greater than or equal to 500 nm.
[0088] Because the main film layer close to the substrate needs to resist stress concentration caused by deformation of the substrate during long-term use, it bears most of the shear strain. In order to prevent interfacial peeling of the composite film and the substrate, the thickness of the sub-composite layer between the primer layer and the transition film layer in the composite film is greater than or equal to 400 nm, including but not limited to 486 nm, 527 nm, 542 nm, etc., and other values within the above range can also be used.
[0089] Since the AlSiON film layer contains a nano-pore structure, the internal structure inevitably has a certain degree of crystal defects. In order to avoid the crystal defects of the AlSiON film layer affecting the internal stability of the composite film through interlayer stress, the thickness of the sub-composite layer between the AlSiON film layer and the transition film layer is greater than or equal to 500 nm, including but not limited to 609 nm, 669 nm, 732 nm, etc., and other values within the above range can be used.
[0090] In the present application, the thickness of the composite film is greater than or equal to 1100 nm, and in an optional embodiment, the thickness of the composite film is 1100 nm-1800 nm, including but not limited to 1576 nm, 1635 nm, 1691 nm, etc., and other values within the above range can be used.
[0091] In the present application, the number of layers of the composite film can be designed and adjusted according to actual application requirements. Specifically, the number of layers of the composite film can be 15 layers, 16 layers, etc.
[0092] In some specific embodiments, the thickness of the primer layer, the first refractive index layer, the second refractive index layer, the transition film layer, the AlSiON film layer and the functional film layer in the composite film can be set to 50-150 nm, for example, it can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, etc., and other values within the above range can be used.
[0093] The present application also provides a preparation method of the above-mentioned composite film, comprising:
[0094] Preparing a substrate, forming an initial composite layer on the substrate, and the AlSiON film layer on the side of the initial composite layer away from the substrate;
[0095] Forming a nano-pore on the surface of the AlSiON film layer away from the initial composite layer to obtain the composite film.
[0096] When the composite film includes a functional coating, the above preparation method further comprises: coating a coating liquid for forming a functional coating on the surface of the AlSiON film layer with a nano-pore to form the functional coating.
[0097] When a primer layer is provided between the main film layer and the substrate, the above preparation method further comprises: forming a primer layer on the substrate before forming the initial composite layer.
[0098] Specifically, when forming the primer layer, the initial composite layer and the AlSiON film layer on the surface of the substrate, a physical vapor deposition (PVD) technique can be used, and in some specific embodiments, the specific process of the PVD technique used in the present application includes the following steps:
[0099] ICP ion cleaning of the substrate for 30-120s to remove surface residual dirt;
[0100] Put the substrate into the coating machine cavity, close the cavity door to pump, and import the process file; the vacuum of the coating machine cavity reaches 2.0-4.0x10 -3 Pa, start depositing the composite film layer;
[0101] When depositing the primer layer, different sputtering target materials are selected according to different materials: the sputtering target material power is 5-10kw, the target argon flow is 100-200sccm, the ICP power is 1-3kW, the argon flow is 80-120sccm, and the oxygen flow is 180-300sccm;
[0102] When depositing the second refractive index film layer, different sputtering target materials are selected according to different materials: the sputtering target material power is 5-10kw, the target argon flow is 100-200sccm, the ICP power is 1-3kW, the argon flow is 80-120sccm, and the oxygen flow is 180-300sccm;
[0103] When depositing the first refractive index film layer, different sputtering target materials are selected according to different materials: the target power is 5-10kw, the target argon flow is 100-200sccm, the ICP power is 1-2kW, the argon flow is 80-120sccm, and the nitrogen flow is 180-300sccm.
[0104] When depositing the transition film layer, different sputtering target materials are selected according to different materials: the target power is 5-10kw, the target argon flow is 100-200sccm, the ICP power is 1-3kW, the argon flow is 80-120sccm, and the nitrogen flow is 100-300sccm;
[0105] When depositing the AlSiON film layer, pure aluminum and silicon targets are selected as the sputtering target material: the target power is 5-10kw, the target argon flow is 100-200sccm, the ICP power is 1-3kW, the argon flow is 80-120sccm, the oxygen flow is 180-300sccm, and the nitrogen flow is 80-260sccm.
[0106] It should be noted that when depositing the first refractive index film layer, the second refractive index film layer and the transition film layer of different materials, the sputtering target materials used can be different, and the sputtering process parameters can be the same or different, which can be adjusted according to the sputtering requirements.
[0107] When the composite film includes multiple first refractive index layers and / or multiple second refractive index layers and / or transition film layers, the deposition operations of the first refractive index layer, the second refractive index layer and the transition film layer described above can be repeated according to the processing requirements. The deposition order of each film layer is not further limited here.
[0108] In view of the adhesion of the film layer to the substrate and the stress between the film layers, the surface temperature of the substrate needs to be raised to 60-90°C, for example, 60°C, 70°C, 80°C, 90°C, etc. before film formation. The process of forming the film layer on the substrate can use sputtering or evaporation, etc.
[0109] In some optional embodiments, nano-pores are formed on the side surface of the AlSiON film layer away from the substrate, including: immersing the initial composite layer in an etching solution, and raising the etching solution to 50-60°C for 2-5 min, and then raising it to 70-80°C for 8-10 min; after the surface forms nano-pores, clean and dry.
[0110] When forming nano-pores on the surface of the AlSiON film layer, the etching solution used includes but is not limited to dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid, phosphoric acid, oxalic acid, citric acid, malonic acid, succinic acid, malic acid, etc. Acidic solutions that can form nano-pores on the surface of the AlSiON film layer can be used as etching solution.
[0111] The present application utilizes the difference in the dissolution behavior of Al, Si, O and N elements in the etching solution and the interfacial selective corrosion of the etching solution to realize the nanoscale surface roughening or pore formation of the AlSiON film layer. In the initial stage of micro-etching, silicon nitride (Si3N4) phase is preferentially dissolved, and the dissolution of silicon oxide (SiO2) also occurs simultaneously with the dissolution of Si3N4. The accelerated dissolution of the two forms a honeycomb-like nano-pore in the silicon-rich region of the AlSiON film layer. At the same time, the Al-O-N phase corrodes slowly, and an AlF3·xH2O passivation film is formed on the surface to inhibit further corrosion. Due to the difference in bond energy between Si-N (439 kJ / mol), Al-O (511 kJ / mol) and Al-N (615 kJ / mol), the acid in the etching solution cuts along the grain boundaries or defects longitudinally, thereby forming nano-channels of a certain depth.
[0112] It is easy to understand that the temperature and time of the micro-etching treatment can be limited in order to obtain a desired nano-pore structure. In some alternative embodiments, the initial composite layer is immersed in an etching solution, and the etching solution is heated to 50-60°C, for example 50°C, 55°C, 60°C, etc., for 2-5 min, and then heated to 70-80°C, for example 70°C, 75°C, 80°C, etc., for 8-10 min.
[0113] The application also provides a structural member comprising the composite film or the composite film prepared by the above method.
[0114] In some embodiments, the structural member can further comprise a metal member, and the composite film is arranged on the surface of the metal member. In particular, the structural member can be a key of an electronic product, and the structural member has excellent wear resistance and use stability.
[0115] The application also provides an electronic product comprising the structural member as a key. The key of the electronic product is not easily damaged, the key mark is not easily scratched, and the key has a long service life.
[0116] The technical solutions of the application are described in more detail below through specific examples.
[0117] Example 1
[0118] The target composite film has 15 layers and a total film thickness of 1576 nm. Al2O3 is selected as the undercoat layer material, SiN and AlN are selected as the first refractive index film layer materials, SiO2 is selected as the second refractive index film layer material, and AlSiN is selected as the transition film layer material. According to the film layer structure diagram, the corresponding film layers are sequentially deposited on the substrate. The specific preparation steps of the composite film are as follows: Figure 3
[0119] Film plating:
[0120] 1. Select aluminum alloy as the substrate, and perform ICP ion cleaning on the substrate for 100 s to remove surface residual dirt.
[0121] 2. Put the substrate into the plating machine cavity, close the cavity door to pump down, and import the process file. When the plating machine cavity vacuum reaches 3.0x10 -3 Pa, start depositing the composite film.
[0122] 3. When depositing the Al3O2 undercoat layer, use pure aluminum target as the sputtering target material: the target material power is 8 kW, the target material argon flow rate is 180 sccm, the ICP power is 2 kW, the argon flow rate is 100 sccm, and the oxygen flow rate is 200 sccm.
[0123] 4. When depositing SiO2 film, a pure silicon target is selected as the sputtering target material: the target power is 8 kW, the target argon flow rate is 180 sccm, the ICP power is 2 kW, the argon flow rate is 120 sccm, and the oxygen flow rate is 260 sccm.
[0124] 5. When depositing AlN films, pure aluminum targets are selected as sputtering targets: the target power is 6 kW, the target argon flow rate is 200 sccm, the ICP power is 2 kW, the argon flow rate is 100 sccm, and the nitrogen flow rate is 280 sccm.
[0125] 6. When depositing AlSiN films, pure aluminum and pure silicon targets are selected as sputtering targets, and aluminum and silicon are sputtered simultaneously: the target power is 6 kW, the target argon flow rate is 200 sccm, the ICP power is 2 kW, the argon flow rate is 120 sccm, and the nitrogen flow rate is 280 sccm.
[0126] 7. When depositing SiN films, a pure silicon target is selected as the sputtering target material: the target power is 8 kW, the target argon flow rate is 180 sccm, the ICP power is 2 kW, the argon flow rate is 120 sccm, and the nitrogen flow rate is 200 sccm.
[0127] 8. When depositing SiO2 film, a pure silicon target is selected as the sputtering target material: the target power is 8 kW, the target argon flow rate is 180 sccm, the ICP power is 2 kW, the argon flow rate is 120 sccm, and the oxygen flow rate is 260 sccm.
[0128] 9. When depositing AlSiON films, pure aluminum and silicon targets are selected as sputtering targets: the target power is 8 kW, the target argon flow rate is 200 sccm, the ICP power is 2 kW, the argon flow rate is 120 sccm, the oxygen flow rate is 180 sccm, and the nitrogen flow rate is 180 sccm.
[0129] During the formation of the composite film, steps 3, 4, 5, 6, 7, 8, and 9 are repeated until the total number of layers (Al3O2 underlayer, SiO2 film, AlN film, AlSiN film, SiN film, and AlSiON film) reaches 14, with a thickness of 1551 nm. This includes 1 Al3O2 underlayer, 6 SiO2 films, 5 AlN films, 1 AlSiN film, 5 SiN films, and 1 AlSiON film.
[0130] Formation of nanopores:
[0131] Into a 2000ml beaker, add 5g 60% sulfuric acid, 2g 80% phosphoric acid and 1000ml pure water, mix and stir to obtain a mixed acid solution; immerse the AlSiON film layer in the mixed acid solution, heat to 50°C for 2 minutes, then heat to 70°C for 8 minutes; after etching, take out and ultrasonic clean in deionized water for 30 minutes; the surface microstructure of the AlSiON film layer after forming nanometer hole structure is shown in Figure 4 .
[0132] Evaporate the functional coating:
[0133] Evaporate the AF anti-fingerprint and waterproof coating on the surface of the AlSiON film layer after cleaning and drying by evaporation method, and the thickness of the flat part of the AF anti-fingerprint and waterproof coating is 25nm.
[0134] The longitudinal section microstructure of the obtained composite film is shown in Figure 5 .
[0135] Example 2
[0136] The target composite film has 15 layers and a total film thickness of 1691nm. The material selection, film layer position setting and coating process are the same as in Example 1.
[0137] Form nanometer holes:
[0138] Into a 2000ml beaker, add 8g 40% hydrochloric acid, 1g 60% sulfuric acid and 1000ml pure water, mix and stir to obtain a mixed acid solution; immerse the AlSiON film layer in the mixed acid solution, heat to 45°C for 10 minutes; take out and ultrasonic clean in deionized water for 30 minutes.
[0139] Evaporate the functional coating:
[0140] Evaporate the functional coating:
[0141] Evaporate the AF anti-fingerprint and waterproof coating on the surface of the AlSiON film layer after cleaning and drying by evaporation method, and the thickness of the flat part of the AF anti-fingerprint and waterproof coating is 25nm.
[0142] Example 3
[0143] The target composite film has 15 layers and a total film thickness of 1635nm. The material selection, film layer position setting and coating process are the same as in Example 1.
[0144] Form nanometer holes:
[0145] A 2000ml beaker was added with 10g of 80% phosphoric acid solution, 1g of 60% nitric acid and 1000ml of pure water, mixed and stirred to obtain a mixed acid solution; the AlSiON film layer was immersed in the mixed acid solution, heated to 60°C for 2 minutes, then heated to 80°C for 10 minutes; after etching, it was taken out and cleaned in deionized water for 30 minutes.
[0146] Evaporating the functional coating:
[0147] The surface of the AlSiON film layer after cleaning and drying was coated with an AF anti-fingerprint and waterproof coating by evaporation method, and the thickness of the flat part of the AF anti-fingerprint and waterproof coating was 25nm.
[0148] Example 4
[0149] Similar to Example 1, except that when forming the nano-pores, the second heating was to 80°C for 10 minutes, and the average pore size of the obtained nano-pores was 25nm and the average depth was 55nm.
[0150] Example 5
[0151] Similar to Example 1, except that when forming the nano-pores, the AlSiON film layer was treated with the mixed acid solution at 28°C for 30 minutes, and the average pore size of the obtained nano-pores was 30nm and the average depth was 12nm.
[0152] Example 6
[0153] Similar to Example 1, except that the thickness of the AlSiON film layer was 150nm.
[0154] Example 7
[0155] Similar to Example 1, except that the thickness of the AlSiN transition film layer was 80nm.
[0156] Example 8
[0157] Similar to Example 1, except that there was no AlSiN transition layer.
[0158] Example 9
[0159] Similar to Example 1, except that the obtained composite film only included an Al2O3 film layer + SiN / SiO2 alternating composite layer + AlSiON film layer + AF anti-fingerprint and waterproof coating, and the total thickness of the SiN / SiO2 alternating composite layer was 1600nm.
[0160] Example 10
[0161] Similar to Example 1, except that there was no Al2O3 primer layer.
[0162] Example 11
[0163] Similar to Example 1, except that no AF fingerprint-proof waterproof coating was applied.
[0164] Example 12
[0165] Similar to Example 1, except that the SiO2 film layer was replaced by SiN film layer and AlN film layer, at this time, the AlN / SiO2 alternating composite layer became AlN / SiN alternating composite layer, and the SiN / SiO2 alternating composite layer became SiN / AlN alternating composite layer.
[0166] Example 13
[0167] Similar to Example 1, except that the SiN film layer and AlN film layer were replaced by SiO2 film layer, at this time, the main film layer was composed of multiple SiO2 film layers + AlSiN transition film layer.
[0168] Comparative Example 1
[0169] Similar to Example 1, except that the average pore size of the nano-pores on the surface of the AlSiON film layer was 3 nm, and the average depth was 7 nm.
[0170] Comparative Example 2
[0171] Similar to Example 1, except that during the formation of the nano-pores, the second heating to 60℃ was for 5 minutes, and the average pore size of the obtained nano-pores was 10 nm, and the average depth was 4 nm.
[0172] Comparative Example 3
[0173] Similar to Example 1, except that there were no nano-pores on the surface of the AlSiON film layer.
[0174] The film thickness and nano-pore size of the composite films obtained in Examples 1-13 and Comparative Examples 1-3 are shown in Table 1.
[0175] Table 1
[0176]
[0177] Performance Test
[0178] The composite films obtained in Examples 1-13 and Comparative Examples 1-3 were subjected to the following performance tests:
[0179] Hardness: according to GB / T 25898-2010;
[0180] Vibration Friction: according to GB / T 2423.10-2008;
[0181] Salt spray corrosion: refer to GB / T 2423.17-2008;
[0182] Steel wire abrasion resistance: refer to GB / T 4802.2-2008;
[0183] Rubber abrasion resistance: refer to GB / T 9867-2008.
[0184] The test results are shown in Table 2, in which, represents no wear or no corrosion; represents slight wear, represents partial wear, represents severe wear; represents slight corrosion; represents moderate corrosion; represents severe corrosion.
[0185] Table 2
[0186]
[0187] It can be seen from the results of Table 1 that the composite film provided by the embodiments has high hardness and excellent corrosion resistance and abrasion resistance. It can be seen from the results of Examples 1-3 that when the average pore size of the nano-pores on the surface of the AlSiON film layer is 10-20 nm and the average depth is 15-30 nm, the obtained composite film has the best performance.
[0188] Compared with Examples 4-5, the composite film obtained in Example 1 has better abrasion resistance and corrosion protection for the substrate. This shows that when the average depth of the nano-pores formed on the surface of the AlSiON film layer is adjusted to 15-30 nm and the average pore size is adjusted to 10-20 nm, a composite film with better abrasion resistance and better corrosion resistance can be obtained.
[0189] Compared with Example 6, the composite film obtained in Example 1 has better abrasion resistance. This shows that by adjusting the thickness of the AlSiON film layer to 200-300 nm, the obtained composite film has better abrasion resistance.
[0190] Compared with Example 7, the composite film obtained in Example 1 has better abrasion resistance. This shows that by adjusting the thickness of the AlSiN transition layer to 100-200 nm, a composite film with better abrasion resistance can be obtained.
[0191] Compared with Example 8, the composite film obtained in Example 1 has better abrasion resistance, which shows that by setting the AlSiN transition layer, the stress change around and inside the composite film can be relieved, thereby improving the bonding force between the inside of the obtained composite film and the substrate, and finally realizing the optimization of the abrasion resistance.
[0192] Compared with Example 9, the composite film obtained in Example 1 has better wear resistance. This shows that by setting the first refractive index layer and the second refractive index layer of different materials to alternately form a composite film, the wear resistance of the obtained composite film can be further improved.
[0193] Compared with Example 10, the composite film obtained in Example 1 has better wear resistance. This shows that the setting of the Al2O3 primer layer can further improve the wear resistance of the obtained composite film.
[0194] Compared with Example 11, the composite film obtained in Example 1 has better corrosion resistance and wear resistance. This shows that the presence of the AF anti-fingerprint waterproof coating can resist the corrosion of salt spray on the obtained composite film, thereby improving the corrosion protection ability of the composite film to the substrate. At the same time, the presence of the AF anti-fingerprint waterproof coating can further improve the wear resistance of the composite film.
[0195] Compared with Example 12, the composite film obtained in Example 1 has better wear resistance. This shows that by using materials with different refractive indices to alternately form different film layers, the wear resistance of the obtained composite film can be further improved.
[0196] Compared with Example 13, the composite film obtained in Example 1 has better wear resistance and better corrosion resistance to the substrate. This shows that by using materials with different refractive indices to alternately form different film layers, the obtained composite film not only has better wear resistance, but also has better corrosion protection to the substrate.
[0197] Compared with Comparative Example 1 and Comparative Example 2, the composite film obtained in Example 1 has better wear resistance. This shows that the size of the nano-pores on the surface of the AlSiON film layer plays a key role in improving the wear resistance of the obtained composite film.
[0198] Compared with Comparative Example 3, the composite film obtained in Example 1 has better wear resistance. This shows that the nano-pore structure on the surface of the AlSiON film layer improves the bonding strength between the functional coating on the surface of the obtained composite film and the main film layer, thereby improving the wear resistance of the obtained composite film.
[0199] Finally, it should be noted that: after considering the specification and practicing the invention disclosed herein, those skilled in the art will easily think of other embodiments of the present application. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or conventional technical means in the art not disclosed by the present application, and is not limited to the precise structure described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof. The scope of the present application is only limited by the appended claims.
Claims
1. A composite film, characterized by, The composite film comprises a main film layer and an AlSiON film layer on at least one side of the main film layer. The AlSiON film layer is provided with nano-holes on the side surface away from the main film layer, and the average pore size of the nano-holes is 4-25 nm.
2. The composite film according to claim 1, characterized by, The average depth of the nano-holes is 5-55 nm.
3. The composite film according to claim 2, wherein, The average pore size of the nano-holes is 10-20 nm. The average depth of the nano-holes is 15-30 nm.
4. The composite film according to any one of claims 1 to 3, characterized in that, The thickness of the AlSiON film layer is greater than or equal to 200 nm, and preferably 200-300 nm.
5. The composite film according to any one of claims 1-4, wherein The main film layer comprises first refractive index film layers and second refractive index film layers arranged alternately. The refractive index of the first refractive index film layers is greater than that of the second refractive index film layers.
6. The composite film of claim 5, wherein, The main film layer further comprises transition film layers. At least one first refractive index film layer and at least one second refractive index film layer form a sub-composite layer, and the transition film layers are located between any two sub-composite layers.
7. The composite film of claim 6, wherein, The materials of the first refractive index film layers in the sub-composite layers on both sides of the transition film layers are different.
8. The composite film according to claim 6 or 7, characterized in that, The refractive index of the transition film layers is greater than or equal to 2.
05. The thickness of the transition film layers is greater than or equal to 100 nm, and preferably 100-200 nm.
9. The composite film according to any one of claims 5 to 8, characterized in that, The material of the first refractive index film layers comprises at least one of SiN, AlN, AlSiN and AlSiON. The material of the second refractive index film layers comprises at least one of SiO2 and Al2O3. The material of the transition film layers comprises AlSiN.
10. The composite film according to any one of claims 1 to 9, characterized in that, The composite film further comprises a functional coating. The functional coating comprises a convex part embedded in the nano-holes on the surface of the AlSiON film layer and a flat part covering the surface of the AlSiON film layer. The thickness of the flat part of the functional coating is 15-35 nm.
11. The composite film according to any one of claims 1 to 10, characterized in that, The composite film further comprises a primer layer on the side opposite to the side of the main film layer where the AlSiON film layer is located. Preferably, the thickness of the primer layer is 5-50 nm. Preferably, the material of the primer layer comprises Al2O3.
12. The composite film of claim 11, wherein, The thickness of the sub-composite layer between the AlSiON film layer and the transition film layer is greater than or equal to 500 nm. The thickness of the sub-composite layer between the primer layer and the transition film layer is greater than or equal to 400 nm.
13. The composite film according to any one of claims 1 to 12, wherein, The thickness of the composite film is greater than or equal to 1100 nm, and preferably 1100-1800 nm.
14. A method of producing the composite film according to any one of claims 1 to 13, characterized by, The method comprises the following steps: Preparation of a substrate, formation of an initial composite layer on the substrate, and the AlSiON film layer on the side away from the substrate; Formation of nano-holes on the surface of the AlSiON film layer away from the initial composite layer to obtain the composite film on the surface of the substrate.
15. The method of claim 14, wherein the composite film is prepared by a method comprising: The method further comprises the following steps: Coating of a coating liquid for forming a functional coating on the surface of the AlSiON film layer with nano-holes to form the functional coating.
16. The method of claim 14 or 15, wherein the method further comprises, The initial composite layer is formed on the substrate, and the preparation method further comprises: forming a primer layer on the substrate before forming the initial composite layer.
17. The method of claim 14-16, wherein the composite film is prepared by a method comprising: The forming of the nano-pores on the side surface of the AlSiON film layer away from the initial composite layer comprises: The initial composite layer is immersed in the etching solution, and the etching solution is heated to 50-60 DEG C and kept for 2-5 min, and then heated to 70-80 DEG C and kept for 8-10 min; after the surface forms the nano-pores, the surface is cleaned and dried.
18. A structural member, characterized by The composite film prepared by the preparation method of any one of claims 14-17.
19. The structural member of claim 18, wherein The structural member comprises a metal member, and the composite film is arranged on the surface of the metal member.
20. The structural member of claim 18 or 19, wherein, The structural member is a key of an electronic product.
21. An electronic product, characterized by The structural member comprises any one of claims 18-20. The structural member comprises any one of claims 18-20.